RISK FACTORS OF SOIL TRANSMITTED HELMINTHS AMONG ELEMENTARY SCHOOL STUDENTS IN CENTRAL SUMBA – WEST NUSA TENGGARA - Mau, Fridolina; Tallan, Mefi Mariana (Journal of Vocational Health Studies, 2023)
Background: Soil Transmitted Helminhs (STH) infection is one of health issues in Indonesia. Helmintiasis is a disease commonly found among elementary school. Purpose: To identify risk factor related to the transmission of infection STH in Central Sumba Regency, East Nusa Tenggara Province. Method: The research was done by analytical description based on cross-sectional study. Primary data on risk factors were colleted by which qustionnaire for students fourth to sixth grade, age ranged 8-15 years old. Diagnosis was established using Kato Katz modification method. The data were is analyzed using by cross-sectional of Chi-square test with confidence interval 95% or p-value <0.05 categorized as significant. Result: The proportion of infection in male was 47.1% and in females was 50.9%. The proportion of STH infections was 83.3%, mostly found in fifth grade children (36.6%) and aged 8-11 years (66.6%). The most common type of worm egg infection found in feces was mixed infection of Ascaris lumbricoides and Trichuris trichiura (35.6%), followed by a single infection with T. trichiura (32.8%) and the least number was A. lumbricoides (14. 9%).STH infections have significant related to some risk factors such as defecating not in the latrine, not washing hand with water and soap before eating and after defecated, not practicing hand washing properly, biting nails, sucking fingers, not cutting nails once a week, and barefood. The highest risk factor of STH infection in Central Sumba was defecating not in the latrine (PR=135.500; CI 95% (34.062 - 539.020)). Conclusion: The proportion of STH infections is still quite high due to low personal hygiene and open defecation.